Normalization of Bullying on TikTok: Audience Reception and Its Implications for Digital Literacy - Reggi Ermila Fasila; Abdul Rasyid (Ali Institute of Research and Publication, 2026)
This study examines the normalization of bullying on TikTok as a form of symbolic violence and explores how audience reception contributes to its social legitimation. Using a qualitative content analysis approach, the study analyzes comments and interactions from selected TikTok videos that contain derogatory expressions, symbolic labeling, and identity-based attacks. The data were collected through purposive sampling and analyzed using coding, categorization, and interpretive analysis based on Stuart Hall’s audience reception framework. The findings show that bullying on TikTok operates not only through direct insults but also through sarcasm, stereotypes, symbolic labeling, and visual cues that subtly degrade individuals. The normalization process occurs through repetitive comments, collective interactions, and digital engagement, such as likes and replies, which function as mechanisms of social validation. Audience reception is dominated by hegemonic and negotiated readings, where derogatory expressions are accepted as humor or ordinary interaction, while oppositional readings remain limited. These findings highlight the need to strengthen critical digital literacy so that users are better able to recognize, resist, and respond to symbolic forms of bullying in digital interactions.